Perspektif Sosiologi terhadap Toleransi dalam Pluralisme Digital: Studi Kasus Program LOGIN Habib Ja'far Channel YouTube @Deddy Corbuzier - Nur Habibah, Jihan; Alia Abdullah, Mirna Nur; Rizaldi, Muhammad Retsa (Jurnal Pancasila dan Kewarganegaraan (JUPANK), 2025)
Digital tolerance and pluralism are important concepts in a society connected through digital technology. Tolerance refers to an attitude of mutual respect for differences, while digital pluralism reflects diversity in the digital space involving various religious and cultural backgrounds. This study examines the sociological perspective on tolerance in digital pluralism through a case study of the LOGIN program hosted by Habib Ja'far and Onadio Leonardo on the @Deddy Corbuzier YouTube channel. The purpose of the study was to understand how pluralism and tolerance are reflected in digital interactions and their influence on audience perceptions of diversity. The approach used was descriptive qualitative with a case study design, using participant observation in the video comment column. The results showed that the LOGIN program succeeded in creating an inclusive dialogue space by presenting speakers from various religious, cultural, and social backgrounds. This program strengthens the message of tolerance and pluralism by inviting viewers to see differences as wealth, not as separators. However, the main challenge in digital pluralism is the potential for misuse of the platform to spread extreme ideologies. The LOGIN program can be a positive example in building tolerance through social media, but it still requires efforts to maintain the quality of discussions and prevent the spread of hatred.